Control of growth: the Drosophila Myc homolog - Gallant, Peter (Henry Stewart Talks, 2010)
The Myc oncogene in vertebrates, Molecular function of Myc, Normal function of Myc, Myc in other taxa, Myc in Drosophila melanogaster, Myc controls animal size, endoreplication, apoptosis, cell competition and asymmetric division, Molecular function of Myc in Drosophila melanogaster, Ribosome synthesis, Max-independent activities, Genetic screening can reveal essential partners for Myc